La ciudad en el Brasil: Por una nueva comprensión del fenómeno urbano brasileño - Teixeira De Godoy, Paulo Roberto [UNESP]; Gilberto De Souza, José [UNESP] (My University, 2013)
The paper presents the analysis of the process of urbanization during the colonial period and the importance of the city to the enterprise of conquest, colonization and formation of the Brazilian territory. The city as a mediation of power relations between Metropolis and Cologne and at the same time, control of production, consumption and circulation of goods, is the starting point for rethinking the trajectory of urbanization in Brazil, surpassing urban-industrial perspective.
The city in Colonial Brazil: A new understanding of Brazilian urban phenomenon
Keywords: Brazil; City; Colonization; Territorial formation